Perceptions of Students’ Executive of the Administrative Processes of a School of Graduate Studies in Ghana. - Hesse, Eugene Kwesi (Ghana Journal of Higher Education Management, 2023)
Although research on students’ perceptions concerning administrative processes in the university they find themselves is burgeoning, little are known about the phenomenon in contexts such as Ghana. The present study analysed the perceptions of the Post Graduate Student Executive of Ghana in the University of Cape Coast. (GRASAG-UCC) on the administrative services provided to them by the School of Graduate Studies, (SGS) UCC, Ghana. The descriptive research design was employed to collect data among 16 GRASAG executives for 2018 to 2020 academic years. The study revealed that the School of Graduate Studies provided competent work, showed interest in students’ welfare and provided adequate administrative assistance. The study also found that SGS can still do more by improving the administrative processes in the office to satisfy the expectation of the executives by involving them in decision making and by establishing facilities to facilitate operations. The following recommendations were given. The School of Graduate Studies should move to a spacious facility to recruit more staff to help execute the plans and duties of the office. The SGS should also collaborate more with GRASAGUCC executives who are the mouthpiece of the postgraduate students in the University